Analisis Defect Produk Material pada Bracket Rear Starter Menggunakan Metode Six Sigma di Pt Otomotif Cikarang - Indi Rahmat Hidayat; Gigih Hapsak Pradipto; Ghina Farhah Azizah (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze and reduce material product defects in the rear starter bracket component at PT Otomotif Cikarang by applying the Six Sigma method through the DMAIC (Define, Measure, Analyze, Improve, Control) approach. PT Otomotif Cikarang faces challenges in maintaining product quality due to material defects that potentially reduce production efficiency and customer satisfaction. Data collection was conducted from September to November 2025, involving a total production of 44,500 units, where 580 defective units were identified. Based on the calculations in the Measure phase, the defect rate was found to be 4,344.5 DPMO (Defects Per Million Opportunities), which is equivalent to a Sigma Level of 4.13 and a product conformity rate (Yield) of 99.57%. Analysis to identified the primary defect types, while root cause analysis was performed using a Fishbone diagram to discover issues across human, method, and material factors. Through the Improve phase, corrective actions were recommended, including strict regulations on the melting material composition in the furnace by limiting scrap return to a maximum of 25% and requiring 75% virgin aluminum ingot to maintain metal ductility. Implementing these proposed improvements is expected to significantly minimize product defect rates toward a higher industrial standard.